Kajian Hak Ulayat Di Kabupaten Kampar Dalam Perspektif Peraturan Perundang-Undangan Dan Hukum Adat - Rika Lestari; Djoko Sukisno (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The existence of ulayat land rights for adat law communities in Kampar Regency is recognized in customary law across generations based on Adat Jati Andiko Nan 44. Development of ulayat land rights arrangements has shifted because they are regulated based on adat law and statutory regulations. The purpose of this research is to examine the recognition and protection of ulayat land rights based on the prevailing laws and regulations and based on adat law. This research method is normative empirical, the data sources are primary data and secondary data and analyzed descriptively qualitatively. The results of the research conclude that the recognition and protection of the ulayat land rights of the adat law community as contained in the statutory regulations have not been able to provide legal protection because the legal politics of recognizing ulayat land rights are still half-hearted, false and ambivalent. Therefore, efforts are needed to rebuild the legal politics of state recognition and protection of ulayat land rights of the adat law communities in the statutory regulations. It is necessary to revise the Kampar Regency Regional Regulation on Ulayat Rights by adopting the values of the Adat Jati Andiko Nan 44 as a law that lives, grows and develops in the adat law communities in Kampar Regency.